A Meta-Analytic Review of Interventions That Promote Meaning in Life. Issue 6 (July 2021) - Manco, Nicholas; Hamby, Sherry
Objective: Increasing meaning in life (MiL) among people experiencing disease or adversity may improve coping and resilience. The purpose of this review is to characterize the effects of MiL interventions. Data Source: A systematic search of PubMed, PsycInfo, and Google Scholar was conducted encompassing the following parameters: meaning in life, purpose in life, or sense of purpose with randomized controlled trials. Study Inclusion & Exclusion Criteria: Randomized controlled trials (RCTs) of interventions with at least one outcome that measured improvement in MiL and were published in English between January 2000 and January 2020. Data Extraction & Synthesis: 33 randomized controlled trials ( k = 35) were identified. Data were coded by authors and a research assistant for intervention type, control group type, and risk of bias. The random effects model of Review Manager 5.3 was used to produce SMD and evaluate heterogeneity. Results: The effect size for studies with a passive control group was SMD = 0.85 (95% CI 0.54 to 1.17) and for studies with an active control group was SMD = .032 (95% CI 0.09 to 0.55). Mindfulness programs produced the largest effect size (1.57) compared to passive controls, while narrative programs produced the largest effect relative to active controls (0.61). There was considerable heterogeneity in most estimates. Conclusion: Several interventions increase MiL, including some that are relatively brief and do not require licensed professionals.